Penerapan Pembelajaran Akhlak Terhadap Keluarga, Tetangga dan Lingkungan - Br Tarigan, Mayang Mustika Dewi; Daulay, Aidil Ridwan; Suryani, Ira; Sukiman, Sukiman (Medan Resource Center, 2023)
The position of morals in human life as social beings has an important role and influence, this is related to the relationship between humans themselves as well as to their environment, whether they are interconnected or otherwise detrimental to each other. In religion itself, morality is not just a polite attitude but more than that it is the basis of a human attitude. Morals as the basis of human discovery with God as the creator and fellow humans as creatures. Morals in Islam itself are attitudes and characters in behavior that are built, one of the thoughts that are non-destructive in nature, contrary to the cultural order and prevailing teachings.